SYNTHESIS, CHARACTERIZATION, ANTI-OXIDANT AND ANTICONVULSANT ACTIVITY OF SYNTHESIZED SCHIFF-BASES THROUGH STRUCTURE ACTIVITY RELATIONSHIP (SAR) STUDY AND ITS EFFECT ON BRAIN GABA LEVEL IN MICE (Journal of Medical & Health Sciences Review, 2025)
Background: Three benzaldehyde derived Schiff-bases (SH 1-3) were synthesized by a condensation reaction from o-phenylenediamine with their respective benzaldehyde derivatives in absolute ethanolic solution under reflux reaction mixture for 6-8 hrs. The structural determinations of the synthesized Schiff-bases were confirmed by FT-IR and 1H-NMR spectroscopy. Benzaldehyde derived Schiff-bases are well-known to possess potent antioxidant and anticonvulsant activities etc. In view of the importance of various benzaldehyde derivatives, the present investigation was undertaken which deals with the structure activity relationship (SAR) study and evaluation of the antioxidant and anticonvulsant activity of synthesized Schiff-bases in mice models.Materials and Methods: DPPH scavenging activity was used to assess the antioxidant activity. Pentylenetetrazole (PTZ) seizure models were used to evaluate the anticonvulsion activity and biochemical evaluation by estimation of brain GABA level of synthesized compounds.Results: In SAR study, the results revealed that the synthesized compounds SH 3, SH 2 and SH 1 at dose of 50 mg/kg show potent pharmacological activities like antioxidant and anticonvulsant activities respectively as compared to the control group at (p